(3QSGdI CMcGe GdaWQI GdESdGejI aj Mce GdTGQH hGddMjIs
(3ChdgG (B:s
(3GdMeO ddg hGdUdGI hGdSdGe Ydi QShd Gddg hHYO bO SFdJ ai JGQjNI SfI SJjf hCda ai Mce bWY GddMjI EPG RGO Ydi GdbHVI gd gh eHGM Ch SfI Ch hGLH s
(3BNQgG (B:s
(3hjMHH CLQI NJGf GdUZjQ Ydi CHjg Ef de jcf dg eGd aef eGdg hCLQI NJGf GdYHO Ydi SjOg cPG ai GdMOGOi hGddg SHMGfI CYde HCMcGe GdaWQI GdESdGejI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs